High-throughput fluorescence assay of cytochrome P450 3A4 - Cheng, Qian (2013)
Microtiter plate-based fluorescence assays allow rapid measurement of the catalytic activities of cytochrome P450 oxygenases (P450s). We describe a high-throughput fluorescence assay of P450 3A4, one of the key enzymes involved in xenobiotic metabolism. The assay involves the oxidative debenzylation of 7-hydroxy-4-trifluoromethyl coumarin, producing an increase in fluorescence.